Nghiên cứu tổng hợp vật liệu BaTiO3 kích cỡ nano bằng phương pháp thủy nhiệt - Hoàn, Nguyễn Xuân; Cẩm Hà, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
The BaTiO3 powders were synthetized by the hydrothermal method in the alkaline solution using the TiCl3 and BaCl2 like precursors. The Ba/Ti initial ratios effect on the formation of BaTiO3 phase was investigeted versus time (at 150°C). The results showed that BaTiO3 powders have right stoichiometric (approximate 1), homogeneous morphology and grain sizes are in the range of 80 - 100 nm.